Definition of Health 2.0 and Medicine 2.0: A Systematic Review - Van De Belt, Tom H; Engelen, Lucien JLPG; Berben, Sivera AA; Schoonhoven, Lisette (JMIR Publications, 2010)
BackgroundDuring the last decade, the Internet has become increasingly popular and is now an important part of our daily life. When new "Web 2.0" technologies are used in health care, the terms "Health 2.0" or "Medicine 2.0" may be used. ObjectiveThe objective was to identify unique definitions of Health 2.0/Medicine 2.0 and recurrent topics within the definitions. MethodsA systematic literature review of electronic databases (PubMed, Scopus, CINAHL) and gray literature on the Internet using the search engines Google, Bing, and Yahoo was performed to find unique definitions of Health 2.0/Medicine 2.0. We assessed all literature, extracted unique definitions, and selected recurrent topics by using the constant comparison method. ResultsWe found a total of 1937 articles, 533 in scientific databases and 1404 in the gray literature. We selected 46 unique definitions for further analysis and identified 7 main topics. ConclusionsHealth 2.0/Medicine 2.0 are still developing areas. Many articles concerning this subject were found, primarily on the Internet. However, there is still no general consensus regarding the definition of Health 2.0/Medicine 2.0. We hope that this study will contribute to building the concept of Health 2.0/Medicine 2.0 and facilitate discussion and further research.